Trend of livestock population and nutritional evaluation of available feed resources in coastal areas of Noakhali district - Rahman, MZ; Ershaduzzaman, M; Huque, KS; Ali, MY (Bangladesh Journal of Animal Science, 2014)
A survey work was undertaken with a total of 200 farm households of the coastal areas of Noakhali were categorized into landless, marginal, small, medium and large based on their landholding and sheep population. All categories of farmers had higher number of sheep compared to goat and cattle. In case of lamb (0-4months) farmers didnt supplied concentrate. The average deficiency of DM (g/h/d), ME (MJ/h/d) and CP (g/h/d) of lamb were 70.24, 0.97 and 13.35, respectively. For growing sheep (4-15 month) small, medium and large farmers provided little but landless and marginal farmers provided very little amount of concentrate. The average deficiency of DM (g/h/d), ME (MJ/h/d) and CP (g/h/d) of growing sheep were 257.31, 2.62 and 34.75, respectively. In case of adult ewe (>15 month, milking) the average deficiency of DM (g/h/d), ME (MJ/h/d) and CP (g/h/d) were 441.87, 2.81 and 35.45, respectively. Livestock farming contributed about 17.2% of annual family income in which the contribution of sheep of the total household income was about 11% followed by goat (3.58%) and cattle (2.62%). The available feed resources were durba, asamilata, chaila, bothoua, gamma, alias grass, shon, bontil, khesari, pakisthani lata, bean leaf, ipil ipil, mayahagoni, kadam, boroi leaf, jackfruit, babla, mango leaf, kitchen wastes, rice straw, and rice bran, til oil cake. Surveyed information on existing available nutrient status of sheep and feed resources would help to develop a feeding system of sheep in coastal areas of Bangladesh. DOI: http://dx.doi.org/10.3329/bjas.v43i3.21652 Bang. J. Anim. Sci. 2014. 43 (3): 213-217